UNDERSTANDING ORGANIZATIONAL CULTURE IN A SMALL FAMILY FIRM - Danda, Gustavo José da Nóbrega; Grzybovski, Denize (REGEPE Entrepreneurship and Small Business Journal, 2015)
The purpose of this study is to investigate the characteristics of organizational culture that fosters entrepreneurship in family firms. The entrepreneurial process is viewed as radical change in family firms due to emotions related to change in this kind of organization, which are more intense than nonfamily firms and makes the organization behaves the same way of previous generation. The culture of family firm Alfa is analyzed through the model of Hall, Melin and Nordqvist (2001) which classifies family business culture according to the fact that it is dominated by one or several family members, the degree of culture explicitness and cultural openness. A single case study was conducted and semi-structured interviews were made with family and non-family members of the family firm Alfa. It was concluded that, despite the fact the employees feel comfortable to express their ideas and critics, the values and norms are not clearly stated and the culture is dominated by the influence of the founder. These last two characteristics damage the entrepreneurial process in the family firm analyzed.